Determinasi Faktor yang Mempengaruhi Agresivitas Pajak Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Sartika Wulandari; Rachmawati Meita Octaviani; Widhian Hardiyanti; Fasya Fadhila (ITB AAS INDONESIA, 2022)
Corporate tax aggressiveness arises from the company's view that the tax burden is an obligation that must be paid. This study aims to provide empirical evidence regarding the effect of CSR, inventory intensity, institutional ownership, and independent commissioners on tax aggressiveness, either simultaneously or partially in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. By using purposive sampling technique, 243 observations were obtained. Data analysis technique using Eviews. The results of this study indicate that CSR and institutional ownership have a significant negative effect on tax aggressiveness, while inventory intensity and independent commissioners have no effect on tax aggressiveness. For further research, other independent variables can be used that may be related to tax aggressiveness, such as KAP specialization, company risk, tenure of directors, deferred tax burden, management compensation, and executive incentives. In addition, it can also examine samples from sectors other than manufacturing.